Impact of Jakarta FIR Realignment on ATC Workload: Case Study of Upper Pangkalpinang Sector - Faisal Halim Setyadi; Rany Adiliawijaya Putriekapuja; Susi Suhardianti (CV. AFDIFAL MAJU BERKAH, 2026)
The rapid development of Indonesia’s aviation industry necessitated the optimization of airspace management to enhance flight safety and efficiency. One strategic effort was the realignment of the Jakarta Flight Information Region (FIR) in March 2024. This study aims to examine the impact of this realignment on the workload of Air Traffic Controllers (ATC) in the Upper Pangkalpinang sector. Employing a quantitative correlational method, data were collected through NASA-TLX-based questionnaires distributed to 48 ATC personnel at the Jakarta Air Traffic Service Center (JATSC). Post-realignment data show a significant increase in flight traffic, with an average rise of 2,000 flights per month, contributing directly to higher ATC workload. Statistical analysis revealed a strong positive correlation (r = 0.918) between FIR realignment and ATC workload. Regression analysis indicated that 84.3% of workload variance could be attributed to the FIR realignment. The highest workload dimensions experienced were mental demand, temporal demand, and effort. This study recommends implementing fatigue risk management strategies, upgrading air traffic management (ATM) systems, and providing continuous training to ATC personnel to support operational safety and performance